INCREASING TEACHERS' CAPABILITIES IN ONLINE LEARNING BY USING WHATSAPP DURING THE PANDEMIC AT SDN 18 BENGKALIS - Kamaruddin Kamaruddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Organizing online learning for each educational unit and developing or determining how to provide learning to students could be done by using social media. Choosing social media in carrying out learning is necessary because social media did not recognize space and time, it made it easier to communicate with people who were far apart. Thus, it was necessary to train teachers in using WhatsApp as an alternative to learning by using action research methods or often school action research. This research involved 8 teachers at SDN 18 Bengkalis. The results of the study found that the teachers’ understanding in online learning in Cycle I was 51.13 with sufficient category. After making improvements and seeing reflections from learning, it was continued with cycle II with the results obtained an average of 73.13 with good category while the teacher's ability in learning in cycle I got sufficient category. In cycle II, out of 8 teachers, 2 teachers got very good category and 6 people got good category. In the learning carried out by the teacher using WhatsApp, there was an increase compared to cycle I. In cycle II, the teachers were already able to use WhatsApp in explaining, providing guidance, and also providing tasks that would be done by the teacher.